The secret life of Albert Entwistle - Cain, Matt (Writer) (John Scognamiglio Books/Kensington Books, 2022)
Perfect for fans of Fredrik Backman and TJ Klune, this humorous, life-affirming, and charmingly wise novel tells the story of how the forced retirement of a shy, closeted postman in northern England creates a second chance with his lost love, as he learns to embrace his true self, connect with his community, and finally experience his life's great adventure...--